A Nondestructive Detection Method Based on Target Resonance. Issue 1 (June 2021) - Chen, Lin; Guo, Chunxian; Yinchun, A; Zhang, Huaiqing
Abstract: Conventional eddy current testing (ECT) considers the detected target as an RL series (RLs) circuit. Starts from the problem of grounding grid break point detection, this paper proposes a detection method based on RLC series (RLCs) circuit resonance since a break point introduces a capacitor for the detection target. When the RLCs target circuit is coupled with the transmitter coil, the input impedance-frequency curve changes significantly. This paper focuses on methodological exploration, and the influences of target coil capacitance, resistance and detection distance on detection system's impedance curve are discussed. Simulation and experimental results show the proposed method can distinguish the RLs and RLCs target circuit, and the detection distance of the RLC target is much greater than the RL target detection distance under the same condition. Besides, the feature region, where the impedance curve changes significantly when RLCs circuit is coupled to the transmitting coil, is located near the resonance point of the testing target. Moreover, the detection distance increases with the decrease of the target resistance. In addition, the closer the coil distance is and the smaller the resistance is, the more obvious the feature region will be.